Retransplant and Medical Therapy for Cardiac Allograft Vasculopathy: International Society for Heart and Lung Transplantation Registry Analysis. Issue 1 (14th August 2015) - Goldraich, L. A.; Stehlik, J.; Kucheryavaya, A. Y.; Edwards, L. B.; Ross, H. J.
Abstract : Cardiac retransplantation for heart transplant recipients with advanced cardiac allograft vasculopathy (CAV) remains controversial. The International Society for Heart and Lung Transplantation Registry was used to examine survival in adult heart recipients with CAV who were retransplanted (ReTx) or managed medically (MM). Recipients transplanted between 1995 and 2010 who developed CAV and were either retransplanted within 2 years of CAV diagnosis (ReTx) or alive at ≥2 years after CAV diagnosis, managed medically (MM), without retransplant, constituted the study groups. Donor, recipient, transplant characteristics and long‐term survival were compared. The population included 65 patients in ReTx and 4530 in MM. During a median follow‐up of 4 years, there were 24 deaths in ReTx, and 1466 in MM. Survival was comparable at 9 years (55% in ReTx and 51% in MM; p = 0.88). Subgroup comparison suggested survival benefit for retransplant versus MM in patients who developed systolic graft dysfunction. Adjusted predictors for 2‐year mortality were diagnosis of CAV in the early era and longer time since CAV diagnosis following primary transplant. Retransplant was not an independent predictor in the model. Challenges associated with retransplantation as well as improved CAV treatment options support the current consensus recommendation limiting retransplant to highly selected patients with CAV. Abstract : This analysis of the International Society for Heart and Lung Transplantation Registry compares adult heart transplant recipients with cardiac allograft vasculopathy who were retransplanted versus those who were managed medically and found similar survival rates at 9 years, supporting the current consensus recommendation limiting heart retransplant to highly selected patients with the condition.